Metal-non-tolerant ecotypes of ectomycorrhizal fungi can protect plants from cadmium pollution - Zhang, Taoxiang; Pang, Wenbo; Yan, Tianyi; Zhang, Panpan; He, Juan; Rensing, Christopher; Yang, Wenhao; Lian, Chunlan (Frontiers in Plant Science, 2023)
The application of mycorrhizal as a bioaugmentation technology for phytoremediation of heavy metal (HM) contaminated soil has attracted widespread attention. In order to explore whether the adaptation of Pinus massoniana (P. massoniana) to metal polluted soil depends on the metal adaptation potential of their associated ectomycorrhizal fungi (ECMF), we evaluated the cadmium (Cd) tolerance of 10 ecotypes of Cenococcum geophilum (C. geophilum) through a membership function method, and P. massoniana seedlings were not (NM) or inoculated by Cd non-tolerant type (JaCg144), low-tolerant (JaCg32, JaCg151) and high-tolerant (JaCg205) isolate of the Cg were exposed to 0 and 100 mg•kg -1 for 3 months. The result showed that, each ecotype of C. geophilum significantly promoted the growth, photosynthesis and chlorophyll content, proline (Pro) content and the activity of peroxidase (POD) of P. massoniana seedlings, and decreased malonaldehyde (MDA) content and catalase (CAT) and superoxide dismutase (SOD) activity. The comprehensive evaluation D value of the tolerance to Cd stress showed that the order of the displaced Cd resistance of the four ecotypic mycorrhizal P. massoniana was: JaCg144 > JaCg151 > JaCg32 > JaCg205. Pearson correlation analysis showed that the Sig. value of the comprehensive evaluation (D) values of the strains and mycorrhizal seedlings was 0.077 > 0.05, indicating that the Cd tolerance of the strain did not affect its regulatory effect on the Cd tolerance of the host plant. JaCg144 and JaCg151 which are non-tolerant and low-tolerant ecotype significantly increased the Cd content in the shoots and roots by about 136. 64-181.75% and 153.75-162.35%, indicating that JaCg144 and JaCg151were able to effectively increase the enrichment of Cd from the soil to the root. Transcriptome results confirmed that C. geophilum increased the P. massoniana tolerance to Cd stress through promoting antioxidant enzyme activity, photosynthesis, and lipid and carbohydrate synthesis metabolism.